2013
DOI: 10.1371/journal.pone.0064564
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronary Tortuosity on Coronary Blood Supply: A Patient-Specific Study

Abstract: BackgroundTortuous coronary arteries are commonly observed in clinical screenings and it may cause a reduction of the coronary pressure. However, whether this reduction leads to significant decreasing in the coronary blood supply is still unknown. The purpose of this study was to investigate the effect of the coronary tortuosity (CT) on the coronary blood supply.MethodA computational fluid dynamics (CFD) study was conducted to evaluate the impact of tortuosity on the coronary blood supply. Two patient-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
1
29
0
1
Order By: Relevance
“…Meticulous vessel preparation with pre-dilatation, use of short stents with thinner structures, guidewires with magnetic navigation systems, use of a second guidewire for material progression ("buddy wire technique and "crooked buddy technique"), and use of the "over the wire" [36][37][38][39][40][41] system are employed. Once the lesion is overpassed with the guidewire, it may be difficult to recognize the location to implant the stent due to the rectification of the tortuous segment and appearance of phantom lesions -Concertina effect.…”
Section: Coronary Tortuosity and Coronary Angioplastymentioning
confidence: 99%
“…Meticulous vessel preparation with pre-dilatation, use of short stents with thinner structures, guidewires with magnetic navigation systems, use of a second guidewire for material progression ("buddy wire technique and "crooked buddy technique"), and use of the "over the wire" [36][37][38][39][40][41] system are employed. Once the lesion is overpassed with the guidewire, it may be difficult to recognize the location to implant the stent due to the rectification of the tortuous segment and appearance of phantom lesions -Concertina effect.…”
Section: Coronary Tortuosity and Coronary Angioplastymentioning
confidence: 99%
“…Presumably, in the absence of any sign of vasospasm, tortuous coronary anatomy may be also partly responsible for distal ischemia in our patients, as a recent retrospective case–control study showed about relation between TTC and coronary abnormalities (Arcari et al., ). Catecholamine surge may precipitate ischemia by increasing myocardial metabolic demand, and may compromise the blood flow in tortuous vessels, as illustrated in computational, in vivo and in vitro models (Han, ; Xie, Wang, Zhu, Zhou, & Zhou, ). Local intermittent microvascular constriction, maybe induced by neuropeptide‐Y released from sympathetic fibers, may also not be excluded (Yalta, Sivri, & Yalta, ).…”
Section: Discussionmentioning
confidence: 99%
“…12 The axis of the CT model was projected onto a reference plane to generate the axis of the nCT model. By using this method, the tortuosity was removed from the CT model while the curvature of the CT model (the curvature of the heart) was retained.…”
Section: Vascular Geometry Reconstructionmentioning
confidence: 99%
“…By using this method, the tortuosity was removed from the CT model while the curvature of the CT model (the curvature of the heart) was retained. 12 Compared to nCT models, the tortuous coronary arteries have some bend sections and are longer than nCT models. Thus, the two important geometry changes (bend sections and lengthen effect) caused by tortuosity are both included and the constructed nCT models were physiological.…”
Section: Vascular Geometry Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation